2000
DOI: 10.1111/j.1471-0307.2000.tb02666.x
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the detection of synthetic milk in dairy milk: 1. Detection of urea

Abstract: A qualitative test for the detection of externally added urea (as synthetic milk) was developed using soybean urease. The quantitative detection of synthetic milk in dairy milk could be achieved by this method based on the ‘a’ value of ‘L, a, b’ scale of the HunterLab colorimeter and also by the diacetyl complexation method. Both methods are sensitive enough to detect amounts as low as 2% synthetic milk added to dairy milk, corresponding to 20 mg of added urea per 100 ml. This work reports on methods to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…To prepare synthetic milk and to increase the SNF (Solid Not Fat) value, urea added to natural milk is 0.2-0.7 mg/ml [26,27]. In our Table 4.…”
Section: Ureamentioning
confidence: 98%
“…To prepare synthetic milk and to increase the SNF (Solid Not Fat) value, urea added to natural milk is 0.2-0.7 mg/ml [26,27]. In our Table 4.…”
Section: Ureamentioning
confidence: 98%
“…Because of the ease of availability of anionic detergents, these are used for emulsification of added fat of non milk origin. The other ingredients being used for synthetic milk formulation include urea, salt, soda, sucrose, vegetable oils, skim milk powder and water (Amrutkar, 2008;Bansal & Bansal,1997;Paradkar et al, 2000a;Paradkar, Singhal, & Kulkarni, 2000b). The liquid thus formed has the appearance of genuine milk (i.e., colour, consistency) and it has been reported to be able to be used for the adulteration of dairy milk at a level of 5e10% (Paradkar et al, 2000a).…”
Section: Introductionmentioning
confidence: 96%
“…Milk has been reported to be adulterated with chemical substances (Arora et al 2004;Souza et al 2011). White colored milk-like preparation, produced by blending a well-designed assortment of urea, detergent, vegetable oil, neutralizers, sugar and water (Bansal and Bansal 1997;Paradkar et al 2000aParadkar et al , b, 2001Jha and Matsuoka 2004;Amrutkar 2008) is reported to be added into milk. Reports have been received that large quantities of such spurious and fatal product have found their way into the market.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have been received that large quantities of such spurious and fatal product have found their way into the market. Detergent is believed to be one of the essential components of such milk-like preparation and is foreign to pure milk (Paradkar et al 2000a(Paradkar et al , b, 2001Sadat et al 2006). Detergent is added to emulsify foreign fat from non-milk origin, which is added as a substitute for milk fat (Paradkar et al 2001;Barui et al 2012).…”
Section: Introductionmentioning
confidence: 99%